Pemanfaatan Instagram Sebagai Media Komunikasi Pemasaran Vendor Wedding Momen Terbaik Photography - Triyandartoko, Adhi; Riyanto, Buddy; Sarjono, Herning Suryo (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
The Utilization of Instagram Social Media as a Marketing Communication Tool for Wedding Vendors, Specifically in the Photography Industry with a Focus on Best Moments Wedding Photography Vendor, Continues to Experience Technological Advancements. The purpose of writing this Scientific Study is to understand how Best Moments Wedding Photography Vendor utilizes Instagram as a marketing communication medium to increase the number of wedding photography service users and the planning process. The author collects, analyzes, reviews literature, and conducts documentation studies of content posted by the Best Moments Wedding Photography Instagram account, as well as conducts interviews with the vendor owner. The research results show that the Best Moments Wedding Photography account utilizes Instagram as a marketing communication medium by following the G-P-A pattern: setting goals (Goals), marketing communication planning (Plan), and actions (Actions), simultaneously applying the repeated exposure theory by using Instagram ads features to reach potential clients more efficiently, resulting in an increase in the number of customers.